Analisa Usability Menggunakan Metode Heuristic Evaluation dan End User Computing Satisfaction pada Website Infobengkel - Bernardito Jordan; Agung Triayudi; Ben Rahman (STMIK Budi Darma, 2022)
Infobengkel website is a website that provides information about available workshops in a certain area. With this, users can find information about the workshop they want easily and quickly. in this study to analyze the usability of the infobengkel website assisted by the Heuristic Evaluation method and End User Computing Satisfaction. both methods are used to analyze the usability of the website and measure the level of user satisfaction of the website. from the results of the study it was stated that the website of workshop information was satisfied by the users. where the End User Computing Satisfaction method gets a value of 7.326 or 73.26% while for the Heuristic Evaluation method it gets a value of 7.204 or 72.04%. After doing the analysis, we get several recommendations for improvement that need to be considered in the website, such as the Format variable in the End User Computing Satisfaction method and the Aesthetic and Minimalist Design variable and Help and Documentation in the Heuristic Evaluation method.